A Study of Reading Comprehension Ability and Group Working Behaviors of the Sixth Grade Students by Using CIRC Learning and Mind Mapping - Pandchaiyopanth, Wacharati; Chatbutra, Wirawan (Ratchaphruek Journal, 2020)
This research was the study of reading comprehension ability and group working behavior by using CIRC learning with mind mapping. It aimed to: 1)compare reading comprehension ability of the grade sixth students before and after, and compare students’ achievement with the designated 70%; and 2) compare group working behaviors before and after the lessons. The sample group of 18 students drawn of the sixth grade students in the second semester, academic year 2018-2019 from Bannhongtakaew School Nakhon Ratchasima Primary Education Service Area Office 4. Research tools were the lesson plans, analysis reading comprehension ability form, and the group working behaviors observation form. Statistics used for data analysis were mean, percentage, standard deviation and t-test (t-test for dependent and t-test for one sample). The research revealed that 1) The post-test score was higher than pre-test with statistical significance at the .05 level. The analytical post teaching score of the reading comprehension ability of the sixth grade students by using CIRC learning and Mind mapping was higher than 70% by the designated criteria with the statistical significance at the .05 level. The analytical score of group working behaviors with sixth grade students by using CIRC learning and Mind mapping was higher than those before with statistical significance at the .05 level.